2018
DOI: 10.1016/j.jhep.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of enterocytes and nitration of junctional complex proteins promote alcohol-induced gut leakiness and liver injury

Abstract: Binge alcohol exposure causes gut leakiness, contributing to increased endotoxemia and inflammatory liver injury. Our results demonstrated for the first time the critical roles of apoptosis of enterocytes and nitration followed by ubiquitin-dependent proteolytic degradation of the junctional complex proteins in promoting this gut leakiness and endotoxemia. These results provide insight into the molecular mechanisms of alcohol-induced inflammatory liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
122
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(154 citation statements)
references
References 36 publications
14
122
0
Order By: Relevance
“…Recently, our group reported that CYP2E1 is also involved in n-6 fatty acid containing western-style high-fat diet induced non-alcoholic steatohepatitis [14] and aging-related liver and kidney damage [15] , [16] through increasing the oxidative and nitrative (nitroxidative) stress. Furthermore, both intestinal and hepatic CYP2E1 induced (i.e., via protein stabilization) by chronic alcohol drinking [17] or binge alcohol exposure seems critically important in promoting alcohol-mediated increased nitroxidative stress, gut leakage, and endotoxemia, contributing to apoptosis of hepatocytes and steatohepatitis [18] , [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group reported that CYP2E1 is also involved in n-6 fatty acid containing western-style high-fat diet induced non-alcoholic steatohepatitis [14] and aging-related liver and kidney damage [15] , [16] through increasing the oxidative and nitrative (nitroxidative) stress. Furthermore, both intestinal and hepatic CYP2E1 induced (i.e., via protein stabilization) by chronic alcohol drinking [17] or binge alcohol exposure seems critically important in promoting alcohol-mediated increased nitroxidative stress, gut leakage, and endotoxemia, contributing to apoptosis of hepatocytes and steatohepatitis [18] , [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that elevated inflammation in the gut combined with high levels of nitrosative stress could affect epithelial junctional complexes such as TJ proteins and contribute to gut leakiness and serum endotoxin levels (Cho et al ., ). TNF‐α, through its receptor TNFR1, is known to contribute to the disruption of TJs and associated dysbiosis (Chen et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Among other functions of miRNAs, miR-155 is involved in the regulation of vascular and endothelial function. Its low regulation is accompanied by reduced inflammation and regeneration processes 22,23 . In addition to these multiple functions, miR-155 is involved in the progression of multiple CNS disorders 24 .…”
Section: Discussionmentioning
confidence: 99%